Aderência e atividade fibrolítica bacteriana ruminal: efeito do pH e da concentração de carboidratos solúveis - Farenzena, Roberta (2010)
In vitro assays were conducted to develop a method to estimate activity of bacterial enzymes in the rumen and the effect of changes in pH (5.5, 6.0, 6.5 and 7.0) and concentration of soluble carbohydrates (0, 100, 200 and 300 mg / dl) on adhesion to forage particles and ruminal bacterial fibrolytic activity. To evaluate the enzymatic extraction methods, samples of ryegrass (Lolium multiflorum) were incubated in a bovine rumen during 24-h and used to obtain enzymatic extracts through different extraction methods: sonication, sonication + lyzozyme, lyzozyme and without previous treatment (control). Then, the enzymatic extract was incubated with carboxymethylcelullose (CMC) and measured the reducing liberated sugars. The enzymatic extraction method did not affect significantly the enzymatic activity, but the standard deviation was lower when extraction only was through sonication. In another methodological assay, the effect of the reaction time between enzymatic extract and substrate on relative enzymatic activity (nmol of reducing sugars/ g DM of sample residue/ min) was tested. The relative activity decreased exponentially with time and stabilized after 240-min of incubation. To evaluate the effects of pH and concentration of sugars on bacterial attachment to feed particles and his degradability, samples of ryegrass (Lolium multiflorum) or cynodon (Cynodon dactilon) were incubated in vitro for 24-h in mediums with different pH (5,5; 6,0; 6,5 or 7,0) or different initial concentrations of glucose (0, 100, 200 and 300 mg/dl). The DM and phosphorus content (phosphorus was assumed be of bacterial origin) were determined in the fermentation residue. In ryegrass samples degradability and the residual phosphorus content were higher than in cynodon (P<0.01) and both factors were affected linearly and positively by pH (<0.01). The increase of soluble carbohydrates concentration exerted linear and negative effects on bacterial attachment (P<0.01), but it did not affected forage degradability. The effect of pH and sugar concentration was evaluated on fibrolityc enzyme activity in residues of the samples incubated in the rumen for 24-h and extracted through sonication. The enzymatic extract was incubated for 240-min with xylan or CMC in reaction mediums with different pH or sugar concentrations. In average, the activity of the enzymes extracted from the ryegrass residue was superior to the cynodon ones (P<0.01). On the other hand, the effect of both factors varied among assays and with the sample type, e.g. in different assays was observed that the pH effect was linear (P<0.05), quadratic (P<0.05) or even do not adjusted to none of the regressions. In the same way, the effect of presence of different concentrations of sugars in the medium on enzyme activity was quadratic mainly (P<0.01). In conclusion, the bacterial attachment to the forage particles was related directly to pH and inversely with concentration of soluble sugars in the incubation medium. However, these effects were less evident on enzymatic fibrolytic activity.